2018
DOI: 10.1016/j.jim.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A secretary bi-cistronic baculovirus expression system with improved production of the HA1 protein of H6 influenza virus in insect cells and Spodoptera litura larvae

Abstract: A bi-cistronic baculovirus expression vector was constructed to facilitate the expression, detection, and isolation of the hemagglutinin (HA) fragment HA1 of H6N1 avian influenza virus (AIV) in an insect and a culture of its cells. In this construct, the GP67sp signal peptide promoted the secretion of the recombinant protein into the culture medium, and improved protein expression and purification. Enhanced green fluorescent protein, co-expressed through an internal ribosome entry site, served as a visible rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…This signal peptide facilitated the necessary posttranslational modifications along with the secretion of the recombinant protein (Targovnik et al 2019). The HA concentration in the hemolymph was around 100fold higher than in Sf21 cell-culture medium (Hsieh et al 2018). In all these reports, the larva-derived HA induced protective immunity in vaccinated mice.…”
Section: Influenza Vaccines and Diagnostic-reagent Productionmentioning
confidence: 91%
See 1 more Smart Citation
“…This signal peptide facilitated the necessary posttranslational modifications along with the secretion of the recombinant protein (Targovnik et al 2019). The HA concentration in the hemolymph was around 100fold higher than in Sf21 cell-culture medium (Hsieh et al 2018). In all these reports, the larva-derived HA induced protective immunity in vaccinated mice.…”
Section: Influenza Vaccines and Diagnostic-reagent Productionmentioning
confidence: 91%
“…Thus, the expression of the HA ectodomain-fused with the retention signal KDEL, the (Lys-Asp-Glu-Leu) endoplasmic-reticulum protein-in T. ni larvae infected with rec-baculoviruses was four-fold higher than that obtained with Sf21 insect cells (Gomez-Casado et al 2011). In addition, the HA ectodomain fused with the viral signal peptide of GP64 was more highly expressed in the hemolymph of Spodoptera litura larvae (Hsieh et al 2018). This signal peptide facilitated the necessary posttranslational modifications along with the secretion of the recombinant protein (Targovnik et al 2019).…”
Section: Influenza Vaccines and Diagnostic-reagent Productionmentioning
confidence: 99%
“…The classical swine fever vaccine, Porcilis Pesti™ (Merck, www.merck.com ) expressed with BEVS was commercially approved in 2010. In addition, baculoviruses, including AcMNPV and BmNPV, have been used to express AVI antigens ([ 12 , 18 , 29 , 32 , 37 ]; Balraj [ 3 ]). The influenza vaccines, Provenge™ (Dendreon, www.dendreon.com ) and FluBlok™ (Protein Sciences Corporation, www.proteinsciences.com ), produced by baculovirus were approved by the Food and Drug Administration in 2010 and 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a baculovirus expression vector system has been widely used for vaccine development due to the versatile features of baculoviruses, such as the large cloning capacity, post-translational modification in a eukaryotic system, replication-defect properties in mammalian cells, and broad tissue tropism [11]. It has also been reported that the HA1 protein of the H6 influenza virus and HA1 protein of the H5N1 AIV can be expressed in insect cells and Spodoptera litura larvae [18,29]; indeed, the avian H7 influenza virus haemagglutinin was expressed in the silkworm (B. mori) pupa [32]. Additionally, recombinant subunit vaccines targeting haemagglutinin have been developed using a baculovirus expression vector system (BEVS).…”
Section: Introductionmentioning
confidence: 99%
“…After enzyme (NEB) digestion, the restriction fragment was column-purified and ligated to the pFastBac1-gp67-His-IRES-EGFP vector. 28 The resultant recombinant plasmid was transformed and amplified in E. coli DH5a, and further transposed into E. coli DH10Bac (Invitrogen) for gene transposition. The transposed bacmid was then purified for transfection and preparation of recombinant baculovirus carrying the gene of interest in Sf9 cells.…”
Section: Immune Gene Activation Of Chbmdcsmentioning
confidence: 99%